2013
DOI: 10.1371/journal.pone.0073343
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Photosensitive Retinal Ganglion Cells in the Diurnal Rodent, Arvicanthis ansorgei

Abstract: Intrinsically photosensitive retinal ganglion cells (ipRGCs) represent a new class of photoreceptors which support a variety of non-image forming physiological functions, such as circadian photoentrainment, pupillary light reflex and masking responses to light. In view of the recently proposed role of retinal inputs for the regulation of diurnal and nocturnal behavior, we performed the first deep analysis of the ipRGC system in a diurnal rodent model, Arvicanthis ansorgei , and compared the anatomical and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 63 publications
6
28
2
Order By: Relevance
“…ipRGCs have not yet been described in the Nile grass rat but they have in a related day-active species, the Sudanese grass rat ( A. ansorgei ). Although several characteristics of these cells are similar to those reported in nocturnal rodents, some differences exist in the firing patterns of a select subtype of ipRGCs ( Karnas et al, 2013a ). The questions of whether ipRGCs co-store PACAP and whether the central projections of these cells are different in diurnal grass rats (either Nile or Sudanese) from those seen in nocturnal rodents have, however, not been addressed.…”
Section: Introductionsupporting
confidence: 56%
“…ipRGCs have not yet been described in the Nile grass rat but they have in a related day-active species, the Sudanese grass rat ( A. ansorgei ). Although several characteristics of these cells are similar to those reported in nocturnal rodents, some differences exist in the firing patterns of a select subtype of ipRGCs ( Karnas et al, 2013a ). The questions of whether ipRGCs co-store PACAP and whether the central projections of these cells are different in diurnal grass rats (either Nile or Sudanese) from those seen in nocturnal rodents have, however, not been addressed.…”
Section: Introductionsupporting
confidence: 56%
“…Rats, as nocturnal animals, generally become more active in response to darkness or low light levels (positive masking) and less active in response to light (negative masking), whilst diurnal animals, such as degus, generally exhibit the opposite response. In any case, the masking effect was more pronounced under RGB (daylight) than under RGV light pulses (nightlight), which also agrees with the fact that ipRGC (sensitive to blue light) are also implicated in masking 44 , 69 . Again, these results could confirm that daylight, but not nightlight, is processed as true light input, activating the masking centres of the circadian system in both degus and rats.…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, electrophysiological recordings showed differences in the photic responsiveness of SCN neurons in degus compared to rats 74 . With regard to the five different ipRGC subtypes (M1-M5), it has been reported that M1, which innervates the SCN (the main pacemaker) exists in a higher percentage (74%) in diurnal species, such as Arvicanthis ansorgei 44 as compared to nocturnal (30–44%), such as mice 42 , 43 , 45 . Thus, the greater cone contingent and higher percentage of M1 ipRGCs in diurnal rodents would explain why rats are unable to entrain under the input contrast between RGB vs .…”
Section: Discussionmentioning
confidence: 99%
“…5), we compared the five ipRGC types’ melanopsin-based spiking responses to light. These analyses are beneficial to the field because MEA spike recordings have been used to compare the melanopsin photoresponses of different types of rodent ipRGCs (Karnas et al, 2013; Perez-Leighton et al, 2011; Tu et al, 2006; Tu et al, 2005) but since this method is done “blind”, researchers have been unable to assign cell types to their recordings. Establishing the correspondence between MEA- and whole-cell-recorded cell types would help overcome this problem.…”
Section: Resultsmentioning
confidence: 99%
“…Melanopsin-positive cells with M1- and M2-like morphologies were detected in Sudanian grass rat, and MEA recordings from neonatal retinas showed three varieties of melanopsin-based photoresponses, suggesting this species might have three or more ipRGC types (Karnas et al, 2013). In rabbit, melanopsin immunohistochemistry revealed not only M1 and M2 cells, but also bistratifying cells that were presumably M3 cells (Hoshi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%